(untitled) (Research, Society and Development, 2021)
Here, we report the findings of a case study (qualitative) addressing issues related to government discourse, with emphasis on economic protection and disregarding the magnitude of COVID-19’s pandemic consequences on the population, instituting misthanasia as a measure of conduct. The decision to prioritize the cases troubles all health services, which might involve abandoning aggravated patients or members of risk groups. We note that the poorly planned mitigation policy and the unbalanced supply-to-demand ratio of health services will cause an increase in the number of fatalities among the cases that could have been avoided, misthanasia. Therefore, we conclude that the number of deaths by COVID-19 might even be hidden; nevertheless, the pain caused by deaths of a political-social etiological nature demonstrates sorrowing, mournful, precocious, and avoidable deceases.